Histopathological changes induced by extracts from the tissue covering the stingers of Potamotrygon falkneri freshwater stingrays - Antoniazzi, Marta M.; Benvenuti, Luiz A.; Lira, Marcela S.; Jared, Simone G. S.; Garrone Neto, Domingos [UNESP]; Jared, Carlos; Barbaro, Katia C. (Pergamon-Elsevier B.V. Ltd, 2011)
Pain is the most conspicuous symptom observed in patients wounded by stingrays, and skin necrosis is common in accidents by freshwater stingrays. The extract from the stinger integumentary tissue of Potamotrygon falkneri containing toxic components (venom) was tested for its ability to induce histopathological changes in the dorsal skin of mice at different times. 3-6 h after injection, foci of necrosis in isolated basal epidermal cells were observed. Full coagulative necrosis of the skin, subcutaneous tissue and skeletal muscle was evident as soon as 24 h after venom exposure, with a clear demarcation from the normal skin. After 48 h, round collections of necrotic cells start to coalesce originating extensive skin necrotic plaques that detach from viable tissue after 72-96 h. Inflammatory infiltrate was observed after 6 h, but was always mild. Acute vascular thrombosis was rare, and hemorrhage was not present at any time. Superficial bacterial infection was present in two of the examined cases. In conclusion, the venom of P. falkneri is responsible for the development of an early necrosis with mild inflammatory reaction, probably due to direct action of the venom. The severe local damage is probably worsened by the mechanical trauma caused by the stinger. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Stingrays; Potamotrygon; Venom; Toxin; Dermonecrosis; Histopathology